2020
DOI: 10.1111/ans.15664
|View full text |Cite
|
Sign up to set email alerts
|

Targeted muscle reinnervation to improve electromyography signals for advanced myoelectric prosthetic limbs: a series of seven patients

Abstract: BackgroundUpper limb amputation is a devastating injury. Patients may choose to use a passive prosthesis, a traditional body‐powered prosthesis or a myoelectric prosthesis driven by electromyography (EMG) signals generated by underlying muscles. Targeted muscle reinnervation (TMR) aims to surgically create strong and reliable signals to permit the intuitive use of a myoelectric prosthesis with the greatest number of movements possible. We review the Alfred Hospital experience of using TMR to improve upper limb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…To enhance neuroprosthetic control, amputation paradigms seeking further reconfiguration of residual limb soft tissues have been developed, including Targeted Muscle Reinnervation (TMR) 17 – 20 , Regenerative Peripheral Nerve Interfaces (rPNIs) 21 – 23 , and the Agonist-antagonist Myoneural Interface (AMI) 24 – 27 . Each of these techniques have been demonstrated in combination with neuroprostheses 17 , 19 , 22 , 24 for the enhancement of prosthetic control. Nevertheless, neuroprosthetic performance is a system-level evaluation that depends on multiple factors such as subject-specific inherent capacities of residual limb motor control and phantom limb perception, engineered functional feedback, presence of visual feedback, and choice of the neuroprosthetic control paradigm.…”
Section: Introductionmentioning
confidence: 99%
“…To enhance neuroprosthetic control, amputation paradigms seeking further reconfiguration of residual limb soft tissues have been developed, including Targeted Muscle Reinnervation (TMR) 17 – 20 , Regenerative Peripheral Nerve Interfaces (rPNIs) 21 – 23 , and the Agonist-antagonist Myoneural Interface (AMI) 24 – 27 . Each of these techniques have been demonstrated in combination with neuroprostheses 17 , 19 , 22 , 24 for the enhancement of prosthetic control. Nevertheless, neuroprosthetic performance is a system-level evaluation that depends on multiple factors such as subject-specific inherent capacities of residual limb motor control and phantom limb perception, engineered functional feedback, presence of visual feedback, and choice of the neuroprosthetic control paradigm.…”
Section: Introductionmentioning
confidence: 99%
“…Those that did not achieve greater degrees of freedom postoperatively reported smoother control of their prosthesis and avoided the need for cocontraction. 9 Only one patient—the only transradial amputation in the series—did not achieve six degrees of prosthetic freedom postoperatively. 9 A study by Hebert et al similarly demonstrated improved myoelectric prosthesis control following delayed TMR, as well as restoration of cutaneous sensation.…”
Section: Discussionmentioning
confidence: 91%
“…9 Only one patient—the only transradial amputation in the series—did not achieve six degrees of prosthetic freedom postoperatively. 9 A study by Hebert et al similarly demonstrated improved myoelectric prosthesis control following delayed TMR, as well as restoration of cutaneous sensation. 5 All patients in this series has transhumeral level amputations.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations